EVALUATION OF EDUCATIONAL PROGRAMS THE DEVELOPMENT OF SPECIALIZATION OF SPAIN POLICE WOMAN WOMEN AND CHILDREN IN WOMAN'S POLICE - Sri Wahyuni; Bedjo Sujanto; Siti Rochana (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to determine the achievement of program objectives with steps to know the implementation of program activities. With qualitative research methods the type of program evaluation. Based on the characteristics of the program to be studied, the Special Education Development Program of Policewomen Police Service Specialist (abbreviated Dikbangspes Ba Police Woman PPA) in Police School of Women, then determined the method used in this research is the CIPP model program evaluation research. This research was conducted in Police School Women, March-July 2017. Instruments used your observation, interview and field documentation. The results of the study were conducted on each component of the evaluation, namely: 1) The context that educational programs for the development of specialization of Police Officers for Women and Children Services are based on the background, legal basis, objectives and targets of the program. 2) Inputs, students who attend meet the requirements of the background assignment, there are a number of educational components that require improvement according to standards such as infrastructure facilities that have not complied with the standard of sleeping rooms are still in the form of dormitory (barracks) los system, teaching materials not yet entirely in the form of modules of the number of subjects that are operated some still in the form of a temporary school text made by educators, 3) The process of learning process is operated with the introduction stage, material depth and rounding / termination phase. The suspicion on the nurturing process is done by daily assessment of mental values. 4) The result of the result of the assessment of the learners is the optimal result with the average value of all reaching the